2021
DOI: 10.1111/mpp.13021
|View full text |Cite
|
Sign up to set email alerts
|

Viral inosine triphosphatase: A mysterious enzyme with typical activity, but an atypical function

Abstract: Plant viruses typically have highly condensed genomes, yet the plant‐pathogenic viruses Cassava brown streak virus, Ugandan cassava brown streak virus, and Euphorbia ringspot virus are unusual in encoding an enzyme not yet found in any other virus, the “house‐cleaning” enzyme inosine triphosphatase. Inosine triphosphatases (ITPases) are highly conserved enzymes that occur in all kingdoms of life and perform a house‐cleaning function by hydrolysing the noncanonical nucleotide inosine triphosphate to inosine mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…To conciliate our result in cassava with that broadly accepted idea, we hypothesise that some plants accumulate unexpectedly high concentration of ITP/XTP in certain subcellular compartments, whereas in those locations where they have damaging consequences, such as in the nucleus, ITP/XTP are kept at much lower concentration. The recent suggestion that euphorbiaceous HAM1-like proteins might harbour a nuclear localization signal [51] fits pretty well with this assumption. Therefore, it is possible that viruses infecting plants from the Euphorbiacea family (e.g.…”
Section: Discussionsupporting
confidence: 57%
“…To conciliate our result in cassava with that broadly accepted idea, we hypothesise that some plants accumulate unexpectedly high concentration of ITP/XTP in certain subcellular compartments, whereas in those locations where they have damaging consequences, such as in the nucleus, ITP/XTP are kept at much lower concentration. The recent suggestion that euphorbiaceous HAM1-like proteins might harbour a nuclear localization signal [51] fits pretty well with this assumption. Therefore, it is possible that viruses infecting plants from the Euphorbiacea family (e.g.…”
Section: Discussionsupporting
confidence: 57%
“…To conciliate our result in cassava with that broadly accepted idea, we hypothesise that some plants accumulate unexpectedly high concentration of ITP/XTP in certain subcellular compartments, whereas in those locations where they have damaging consequences, such as in the nucleus, ITP/XTP are kept at much lower concentration. The recent suggestion that euphorbiaceous HAM1-like proteins might harbour a nuclear localization signal (James et al, 2021) fits pretty well with this assumption. Therefore, it is possible that viruses infecting plants from the Euphorbiacea family (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…As it has been recently reported that plant viruses infecting Euphorbiaceae and especially Manihot esculenta (commonly known as Cassava) possess a homologue of ITPA (James et al, 2021; Leiva et al, 2022), we were curious whether ITP and IDP concentrations change during infection with such a virus. We chose to investigate this question in N. benthamiana because Arabidopsis is not a known host of viruses encoding ITPA.…”
Section: Resultsmentioning
confidence: 99%
“…So far, there have been several sporadic reports about the existence of ITPA in plants (Lin et al, 2001;James et al, 2021), but this enzyme and corresponding mutant plants…”
Section: Discussionmentioning
confidence: 99%